Kepemimpinan Etis dan Sikap Kerja dalam Pendidikan Islam: Peran Moderasi Kebutuhan Otonomi terhadap Kepuasan Kerja dan Komitmen Organisasi yang Afektif - Abdul Mughni Ramadhani Azmy; Fatmah Bagis; Erny Rachmawati; Hengky Widhiandono (Jurnal Ilmiah Ekonomi Islam, 2026)
The changing ethical demands in modern organizations have driven the importance of ethical leadership as a foundation for creating a healthy and quality work environment. This study aims to analyze the influence of perceived ethical leadership on job satisfaction and affective organizational commitment among employees of an Islamic educational institution in Cilacap Regency, as well as to test the role of need for autonomy as a moderating variable and direct predictor. A quantitative approach was used involving 225 respondents selected through purposive sampling. Data were analyzed using SEM-PLS. The results of the study show that ethical leadership has a positive effect on job satisfaction and affective commitment. However, need for autonomy weakened this relationship, indicating that the level of need for autonomy does not change the strength of the influence of leaders' ethical behavior. Nevertheless, the need for autonomy has been shown to have a positive effect on job satisfaction and affective commitment, indicating that the fulfillment of autonomy remains an important factor for employee psychological well-being. These findings provide practical implications for Islamic Education to strengthen the moral role models of leaders and provide proportional autonomy to improve the quality of work and emotional ties of employees to the organization.